Behavioral and molecular responses to electroconvulsive shock differ between genetic and environmental rat models of depression. Issue 2 (30th April 2015) - Luo, Jie; Min, Su; Wei, Ke; Cao, Jun; Wang, Bin; Li, Ping; Dong, Jun; Liu, Yuanyuan
Abstract: Depression׳s causes play a role in individuals׳ different responses to antidepressant treatments, which require advancements. We investigated the mechanisms behind and responses to a highly effective antidepressant treatment, electroconvulsive therapy (ECT), in rat models with different (genetic or environmental) depression causes. Wistar Kyoto (WKY) rats and Wistar rats treated with chronic unpredictable mild stresses (CUMS) were used as genetic and environmental rat models of depression, respectively. The rats underwent electroconvulsive shock (ECS, the animal analog of ECT) or sham ECS. We performed a sucrose preference test, open field test, and Morris water maze to assess behavior. Hippocampal neuron numbers were measured with Nissl stain. Hippocampal BDNF, CREB, and p-CREB proteins were assayed with ELISA or western blotting. The main results showed that ECS impaired WKY rats׳ memories but improved CUMS rats׳ memories. It elevated hippocampal BDNF and CREB proteins only in CUMS rats, while it improved depressive behavior and hippocampal p-CREB protein levels in both rats, with more effective regulations in the CUMS rats. ECS did not change the hippocampal neuron number in both rats. These findings suggest that ECS exerted up-regulating effects on hippocampal BDNF and CREB (and its phosphorylation) in depressed rats, and the environmental model responded better. Highlights: Environmental model of depression responded better to ECS than genetic one. ECS improved memories of environmental model rats but impaired genetic one׳s. ECS improved depressive behavior and elevated hippocampal BDNF and (p-)CREB. Different responses to ECS related to different depression causes, not rat strain. ECS did not regulate the hippocampal neuron numbers in depressed rats.